MODEL PEMBELAJARAN OPEN ENDED SEBAGAI SOLUSI UNTUK MEMAKSIMALKAN HASIL BELAJAR MATEMATIKA SISWA SD - Ningsih, Evi Wahyu; Budianti, Yudi; Sumirat, Fanny (JMIE (Journal of Madrasah Ibtidaiyah Education), 2020)
Learning and intruction of mathematic is a process intended for facillitate condition of student in learning environment atmosphere that will have an impact on increasing student learning outcomes. This study aims to improve student learning outcomes in mathematics in elementary schools. This research used qualitative and emphasize of data analysis processÂ  for comparation conclusion from literature review in several scientific journals. Result of the research show that used the Open Ended Learning model can elevate cognitive aspect in leaning outcomes in mathematics, in other hand can involve all of student to develop their creativity and active in mathematic learning, so that students can feel their confident to built mathematic mind set for answer each of the problems through various strategy. Therefore, this reseach conclude that used Open Ended Learning model as one solution for improve students mathematic learning in elementary schools.Â Â